Community Participation Management in Education at Public Elementary School 04 Manggalewa - Edy Hamidun; Fitri Nur Mahmudah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
The purpose of this study is to determine the management of community participation. This research method uses a qualitative type with a case study approach. The Public Elementary School 04 Manggalewa has conducted the research. The data collection technique in this study used a structured interview using guidelines. Participants were selected using purposive consisting of the principal, teachers, and parents of students. The data analysis technique used the Stake model and analyzed with the Atlas.ti version 8 software. This study's results indicate that community participation management consists of four things, namely, ability, coordination, control, and contribution. This capability needs to be considered for schools in Indonesia in building and developing schools through community involvement. Suggestions to school principals, teachers, and parents to improve relationships and open communication and sustainability in realizing better education.